2019
DOI: 10.1002/anie.201901343
|View full text |Cite
|
Sign up to set email alerts
|

A Tale of Two Trimers from Two Different Worlds: A COF‐Inspired Synthetic Strategy for Pore‐Space Partitioning of MOFs

Abstract: Supportinginformation and the ORCID identification number(s) for the author(s) of this article can be found under: https://doi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 80 publications
(47 citation statements)
references
References 66 publications
1
46
0
Order By: Relevance
“…We hoped to replace these seemingly weakly coordinating ligands with dipyridyls to partition the pore space. [8] Unexpectedly, this solid-state reaction did not proceed despite sufficient pore sizes of 1 a. Notably, we observed that pyridyl monomers could diffuse into the pores and, coordinated to the flanking Cd 2 + instead of replacing the seemingly weakly coordinated DEF solvates.…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…We hoped to replace these seemingly weakly coordinating ligands with dipyridyls to partition the pore space. [8] Unexpectedly, this solid-state reaction did not proceed despite sufficient pore sizes of 1 a. Notably, we observed that pyridyl monomers could diffuse into the pores and, coordinated to the flanking Cd 2 + instead of replacing the seemingly weakly coordinated DEF solvates.…”
Section: Introductionmentioning
confidence: 71%
“…15.5 Å (20.3 Å-2 × CdÀ N bonds with 2.4 Å for each) would replace the two DEF solvates, thus partitioning the pore space. [8] To explore this possibility, we first reacted 1 a with dipyridyl ligands 4,4 ' -bipyridine (Bipy), 4,4 ' -azopyridine (Azopy), trans-1,2bis(4-pyridyl)ethylene (Bpee), and 4,4 ' -dipyridyl sulfide (Dps) in CHCl 3 . [3g,13] However, we found that no obvious substitution reaction occurred and the single-crystals slowly became opaque and then powered.…”
Section: Resultsmentioning
confidence: 99%
“…In both first and second stages, we made use of the coordination assembly only. In the third stage which involves both covalent and coordination bond formation, we showed an example of using in situ formed organic molecule (through trimerization of pyridine‐4‐boronic acid) to direct the pacs formation …”
Section: Figurementioning
confidence: 99%
“…Merging the properties of three‐dimensional buckyballs (or buckybowls) and covalent‐organic frameworks (COFs) provides access to a novel class of materials combining ultrafast energy/electron transport characteristic of three‐dimensional (3D) fulleretic linkers with high modularity, crystallinity, and surface area, which are intrinsic properties of COFs . The precise donor–acceptor alignment achieved in the materials is imposed by the rigid COF scaffold and is crucial for efficient energy or charge transfer as it can influence the distance of exciton diffusion, π–π stacking, or Förster radius, and as a result, can enhance device performance …”
Section: Introductionmentioning
confidence: 99%